Effects of diabetic pharmacotherapy on prolactin hormone in patients with type 2 diabetes mellitus: Bane or Boon - Rasheed, Huda Abdulbaki (J Adv Pharm Technol Res, 2019)
Prolactin is a polypeptide hormone secreted from the anterior part of the pituitary gland which was implicated as a diabetogenic factor in the pathogenesis of type 2 diabetes mellitus (T2DM). Therefore, the aim of the present study was to evaluate prolactin serum levels in patients with T2DM regarding the effect of diabetic pharmacotherapy. Eighty patients with T2DM compared with 25 male healthy controls were recruited and divided into four groups: Group I – 29 patients with T2DM treated with metformin, Group II – 30 patients with T2DM treated with glyburide, Group III – 21 patients with T2DM treated with glyburide plus metformin, and Group IV – 25 control male healthy patients. Prolactin serum levels were high in patients with T2DM compared with controls (P < 0.01). Prolactin serum levels were higher in glyburide-treated patients compared with metformin-treated patients (P < 0.01). This study concludes that high prolactin levels in patients with T2DM are linked with diabetic complications and regarded as a beneficial phenomena to overcome IR and diabetic complications. Metformin but not glyburide reduced prolactin levels due to the improvement of insulin resistance.